Exploring Death Anxiety and Mental Health among Adults Living in Lembah Klang, Malaysia - Mohd Hoesni, Suzana; Hj Manap, Jamiah; Shafurdin, Nurul Shafini; Ibrahim, Muhamad Ariff (Human Resource Management Academic Research Society, 2021)
The study of death anxiety in psychology is increasing however, it is still at its infancy. Thus, this study aims to explore mental health (depression, anxiety and stress) and death anxiety among adults living in Lembah Klang, Malaysia. A number of 309 respondents volunteered to participate in this study and completed the questionnaires. The questionnaires consisted of questions regarding personal background, mental health (depression, anxiety and stress) and death anxiety. Results showed that there was a small, positive and significant correlation between anxiety and death anxiety (cessation) (r=0.17**, p<0.01) and death anxiety (extinction) (r=0.14*, p<0.05). There was also a small, positive and significant correlation between depression and death anxiety (extinction) (r=0.12*, p<0.05). Results also showed that there was a small, negative and significant relationship between age and mental health. Future research recommendation and implication to research and practical perspectives were also discussed.